'Monster cell' melanoma with pulmonary metastasis and cyclin D1 amplification. (21st December 2012) - Hawryluk, Elena B.; Baran, Johanna L.; Gerami, Pedram; Sepehr, Alireza
<x xml:space="preserve">Abstract</x> Markedly pleomorphic epithelioid cells with high mitotic activity, giant cell formation, very large atypical nuclei, multiple nucleoli and abundant cytoplasm characterize 'monster' cells and may indicate aggressive tumor behavior. Very rare reports of melanomas comprised of 'monster cells' or cells with comparable histomorphological features, found in tissue samples from skin, lymph nodes, CNS, oral cavity and ileum have been published in the literature. This case is the first such description in the lung, and it is characterized with a battery of immunohistochemical stains; BRAF mutation status was negative, and fluorescence in situ hybridization analysis revealed increased copy number gains in 11q (cyclin D1), which is associated with poor prognosis in melanoma. The presence of monster cells in melanoma was associated with aggressive behavior in the reported patient.